Developing academic oral skills using the video pitch as a learning strategy - Orfanò, Bárbara Malveira; de Sá, Elisa Mattos; Terra, Lívia (Letras, 2023)
This research reports on the success of an online oral task developed for English for Academic Purposes learners in a Brazilian university context, which required recording and submitting a short video pitch about the students’ own research. We discuss the contributions the task brought to improving oral academic skills, focusing on the videos and comments posted in the online forum, and the students’ self-evaluations. Our results indicate that issues such as identity, agency, and autonomy play an important role in the teaching and learning of EAP and deserve attention when designing materials for students in this specific context.